Uma viagem pelas linguagens: proposta didática de letramento cinematográfico para o ensino fundamental - José Geraldo Pereira de Jesus (2021)
This work is purposeful in view of Resolution No. 003 of June 2, 2020 of the Profletras Management Council. We present a proposal for a systematized didactic sequence, and a theoretical foundation that aim to provide teachers in the final years of elementary school with both theoretical and practical tools for the development of a methodology aimed at multiliteracies through the discursive genre film, from a work with the film and its multi-genres, credit, subtitles, post-credit scene, synopsis, trailer, review. The didactic sequence is guided by the perspectives of Moran (1995) and Napolitano (2004). We also rely on researchers such as Bacich and Moran (2018), Bortoni-Ricardo (2008), Kleiman (2005), Moran (1995), Martin (2005), Napolitano (2004), Rojo (2012), Soares (1995) and others that deal with theories and practices of teaching-learning of reading aiming at multiliteracies. In addition, the Didactic Sequence brings theoretical contributions proposed by Dolz, Noverraz and Schneuwly (2004) and Cosson (2019) that provide us with an instrumental basis on how to organize didactic-pedagogical activities to obtain multiliteracies from a discursive genre, such as also contribute to the greater insertion of students in sociocultural and artistic practices, such as cinema, with a view to human and critical training through them.